METHODOLOGY FOR INNOVATIVE EFFECTIVE ORGANIZATION OF THE EDUCATIONAL PROCESS (Multidisciplinary Journal of Science and Technology, 2024)
This article highlights the possibilities and advantages of using the educational process designed to improve the effectiveness of the educational process when teaching subjects based on digital and pedagogical technologies.